YOUNG CONSUMERS AS GROUP BUYING SERVICES’ CUSTOMERS - Edyta Rudawska (Polityki Europejskie, Finanse i Marketing)
Currently, young consumers are becoming important participants in the market process. It is a consequence of the fact that they have an increasing impact on buying decisions undertaken by the family as well as they have an increasing individual purchasing power resulting from financial resources at their disposal. Economic and social changes have formed a different type of a young consumer, who, among other things, makes more reasonable choices and needs to establish social bonds what, in turn, makes him/her form groups of friends or integrate with others. These tendencies are the bases of new way of buying, the so-called group buying. Group buying can be defined as buying in group with the aim of receiving quantity discounts. The main objective of this paper is to present the research results conducted among university students aimed at identification of students’ buying behaviours on group buying services.